1998
DOI: 10.1108/08876049810202339
|View full text |Cite
|
Sign up to set email alerts
|

Service failure and loyalty: an exploratory empirical study of airline customers

Abstract: Percentage of respondents 1-2 2-3 >3 Key Small mistake Big mistake Figure 3. Percentage of respondents still trusting their airline following a service failure Analyses of buyer-seller relationships Early stages of a relationship

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(128 citation statements)
references
References 36 publications
2
125
0
1
Order By: Relevance
“…At least, service providers should understand customers' early indicators of switching. Bejou and Palmer (1998) demonstrate that the effect of a service failure is in how it affects trust and commitment between the parties in a relationship. They refer to Dwyer, Schurr, and Oh (1987) and their identification of five stages in a relationship.…”
mentioning
confidence: 99%
“…At least, service providers should understand customers' early indicators of switching. Bejou and Palmer (1998) demonstrate that the effect of a service failure is in how it affects trust and commitment between the parties in a relationship. They refer to Dwyer, Schurr, and Oh (1987) and their identification of five stages in a relationship.…”
mentioning
confidence: 99%
“…There is agreement in the literature that a relationship is negatively influenced by service failures (Bejou and Palmer, 1998;Weun et al, 2004). However, there is division regarding whether a relationship of high quality magnifies or buffers the effect of a service failure (Bejou and Palmer, 1998;Hess et al, 2003).…”
Section: Service Failures and Customer Relationshipsmentioning
confidence: 71%
“…Successful service recovery has an influence on customer satisfaction (Smith et al, 1999;Zeithaml et al, 1996) and customer loyalty (Bejou & Palmer, 1998;Maxham & Netemeyer, 2002). Kelley, Hoffman and Davis (1993) suggested that attempts should be made to recover from a service failure.…”
Section: Service Recoverymentioning
confidence: 99%